DESIGN GROUND BASED RADAR BY USING MATLAB SIMULINK (International Journal of Engineering Sciences & Management Research, 2017)
The Purpose of this paper is to study the radar and its basic principles, the characteristic that effect on its parameters and explain its types and its application and study the change of parameters of ground based radar parameters for design ground radar for both target (missile and aircraft). By using (MATLAB Program), a program designed to show the effect of change of same parameter for ground based radar. The change include cross- sectional area of the antenna peak, power transmitted by the radar. Study the effect of radar cross –section on detection range and on peak power when doubling it or halving it.